KONTRIBUSI MINAT KERJA DAN PENGALAMAN PRAKERIN TERHADAPKESIAPAN MEMASUKI DUNIA KERJA - Azmil Kamal; Thamrin Thamrin (Universitas Negeri Padang, 2019)
This research is caused by working interest and industrial internship experience have a contribution on the students’ readiness to face the work field. The aim of this research is to show the contribution of working interest and industrial internship experience on individually or together on readiness to enter the work field. The population of this research is 134 students and the sample study is 58 studentsof SMKN 1 Sintuk Toboh Gadang who have done industrial internship experience. The data of this research is collected by questionnaire distributed to the studentswith using a Likert scale that has tested for validity and reliability. The results of data analysis showed that (1) The working interest and industrial internship experience in together contributed significantly onreadiness to enter the workfield of students by 36.8%. (2) The working interest contributed significantly onreadiness to enter the work field by 11.76%, (3) The industrial internship experience contributed significantly onreadiness to enter the work field by 24.01%. It can be concluded that working interest and industrial internship experience contributed on readiness to enter the work field of the XII grades students of SMKN 1 Sintuk Toboh Gadang, the higher of working interest and the good industrial internship experience, then the higher the readiness to enter the work field. Keywords:the working interest, industrial internship experience, readiness to enter the work field